A relação entre as condições precárias de moradias e a incidência de casos de doenças transmitida pelo Aedes Aegypti - Costa, Josiel Melquiades da (Universidade Federal Rural do Semi-Árido, 2019)
The paper addresses the problem of housing conditions and health problems that affect the lives of many Brazilians. In this context, the objective is to establish a relationship between precarious housing and the high incidence of Aedes Aegypti disease in the city of Angicos / RN. In the analysis of data obtained through home visits, it was found that there are indices that suggest a relationship between precarious housing and the increase of diseases such as: Dengue fever, Chikungunya fever and Zika virus. This relationship is strengthened by the inefficient water supply system in the city, which causes residents to use inadequate water storage facilities, contributing negatively to the high incidence of these diseases.
Artigo Acadêmico
Keywords: Moradias; Aedes Aegypti; Precárias; Abastecimento; Housing; Aedes Aegypti; Precarious; Supply; Storage; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA